Efficacy and safety of dual add‐on therapy with dapagliflozin plus saxagliptin versus glimepiride in patients with poorly controlled type 2 diabetes on a stable dose of metformin: Results from a 52‐week, randomized, active‐controlled trial. Issue 7 (9th March 2020) - Frias, Juan P.; Gonzalez‐Galvez, Guillermo; Johnsson, Eva; Maaske, Jill; Testa, Marcia A.; Simonson, Donald C.; Dronamraju, Nalina; Garcia‐Sanchez, Ricardo; Peters, Anne L.
Abstract: Aims: To evaluate the efficacy and safety of dapagliflozin (DAPA) + saxagliptin (SAXA) compared with glimepiride (GLIM) in patients with type 2 diabetes who were inadequately controlled [glycated haemoglobin (HbA1c) 7.5–10.5% (58–91 mmol/mol)] on metformin monotherapy. Materials and methods: This 52‐week, multicentre, double‐blind, active‐controlled study (NCT02419612) randomized (1:1) patients on metformin to add‐on DAPA 10 mg + SAXA 5 mg ( n = 227) or GLIM 1–6 mg (titrated; n = 217). The primary efficacy endpoint was change in HbA1c from baseline to week 52. Results: Baseline mean ± standard deviation of age, duration of diabetes and HbA1c were 56.1 ± 9.7 years, 7.8 ± 6.4 years and 8.5% ± 0.8% (69 ± 9.0 mmol/mol), respectively. Adjusted mean change from baseline in HbA1c was −1.35% (−14.8 mmol/mol) with DAPA + SAXA versus −0.98% (−10.7 mmol/mol) with GLIM ( P  <0.001). Changes from baseline in body weight and systolic blood pressure were −3.1 kg and −2.6 mmHg with DAPA + SAXA versus +1.0 kg ( P  <0.001) and +1.0 mmHg ( P = 0.007) with GLIM. More patients achieved HbA1c <7.0% (53 mmol/mol) (44.3% vs. 34.3%; P = 0.044), and fewer patients required treatment intensification (1.3% vs. 8.8%; P = 0.002) with DAPA + SAXA than with GLIM. Conclusions: Compared with GLIM, concurrent addition of DAPA + SAXA significantly improved glycaemic control, body weight and other metabolic parameters in patients inadequately controlled on metformin. Trial: NCT02419612, ClinicalTrials.gov.